An exploration of ethnomathematics at Sewu Temple in Yogyakarta - Sulistyowati, Dina; Khotimah, Rita Pramujiyanti (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2022)
This study explores the elements of mathematics (geometry and arithmetic) in Sewu Temple. As the research is qualitatively discussed, ethnographic design is appropriately implemented with observation, interviews, and documentation for collecting data. The data analysis technique shares four steps; collecting, reducing, presenting, and drawing a conclusion